Sub-super solutions for (p-q) Laplacian systems

  • Somayeh Haghaieghi1Email author and

    Affiliated with

    • Ghasem Alizadeh Afrouzi2

      Affiliated with

      Boundary Value Problems20112011:52

      DOI: 10.1186/1687-2770-2011-52

      Received: 13 August 2011

      Accepted: 2 December 2011

      Published: 2 December 2011

      Abstract

      In this work, we consider the system:

      { - Δ p u = λ [ g ( x ) a ( u ) + f ( v ) ] in Ω - Δ q v = λ [ g ( x ) b ( v ) + h ( u ) ] in Ω u = v = 0 on Ω , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equa_HTML.gif

      where Ω is a bounded region in R N with smooth boundary ∂Ω, Δ p is the p-Laplacian operator defined by Δ p u = div (|∇u|p-2u), p, q > 1 and g (x) is a C1 sign-changing the weight function, that maybe negative near the boundary. f, h, a, b are C1 non-decreasing functions satisfying a(0) ≥ 0, b(0) ≥ 0. Using the method of sub-super solutions, we prove the existence of weak solution.

      1 Content

      In this paper, we study the existence of positive weak solution for the following system:
      { - Δ p u = λ [ g ( x ) a ( u ) + f ( v ) ] in Ω - Δ q v = λ [ g ( x ) b ( v ) + h ( u ) ] in Ω u = v = 0 on Ω , http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equa_HTML.gif
      (1)

      where Ω is a bounded region in R N with smooth boundary ∂Ω, Δ p is the p-Laplacian operator defined by Δ p u = div(|∇u|p-2u), p, q > 1 and g(x) is a C1 sign-changing the weight function, that maybe negative near the boundary. f, h, a, b are C1 non-decreasing functions satisfying a(0) ≥ 0, b(0) ≥ 0.

      This paper is motivated by results in [15]. We shall show the system (1) with sign-changing weight functions has at least one solution.

      2 Preliminaries

      In this article, we use the following hypotheses:

      (Al) lim f M ( h ( s ) ) 1 q - 1 s p - 1 = 0 http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_IEq1_HTML.gif as s → ∞, ∀M > 0

      (A2) lim f (s) = lim h (s) = ∞ as s → ∞.

      (A3) lim a ( s ) s p - 1 = l i m b ( s ) s q - 1 = 0 http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_IEq2_HTML.gif as s → ∞.

      Let λ p , λ q be the first eigenvalue of -Δ p , -Δ q with Dirichlet boundary conditions and φ p , φ q be the corresponding positive eigenfunctions with ||φ p || = ||φ q || = 1.

      Let m, δ, γ, μ p , μ q > 0 be such that
      | φ p | p - λ p φ p m in Ω ¯ δ φ p μ p on Ω - Ω δ http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equ1_HTML.gif
      (2)
      and
      { | φ q | q - λ q φ q m in Ω ¯ δ φ p μ p on Ω - Ω δ . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equ2_HTML.gif
      (3)
      Ω ¯ δ = { x Ω ; d ( x , Ω ) δ } . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equb_HTML.gif
      We assume that the weight function g(x) take negative values in Ω δ , but it requires to be strictly positive in Ω-Ω δ . To be precise, we assume that there exist positive constants β and η such that g(x) ≥-β on Ω ¯ δ http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_IEq3_HTML.gif and g(x) ≥ η on Ω-Ω δ . Let s0 ≥ 0 such that ηa(s) + f (s) > 0, ηb(s) + h(s) > 0 for s > s0 and
      f 0 = max { 0 , - f ( 0 ) } , h 0 = max { 0 , - h ( 0 ) } . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equc_HTML.gif
      For γ such that γr-1t > s0; t = min {α p , α q }, r = min{p, q} we define
      A = max [ γ λ p η a ( γ 1 p - 1 α p ) + f ( γ 1 q - 1 α q ) , γ λ q η b ( γ 1 q - 1 α q ) + h ( γ 1 p - 1 α p ) ] B = min [ m γ β a ( γ 1 p - 1 ) + f 0 , m γ β b ( γ 1 q - 1 ) + h 0 ] http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equd_HTML.gif

      where α p = p - 1 p μ p p p - 1 http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_IEq4_HTML.gif and α q = q - 1 q μ q q q - 1 http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_IEq5_HTML.gif.

      We use the following lemma to prove our main results.

      Lemma 1.1[6]. Suppose there exist sub and supersolutions (ψ1, ψ2) and (z1, z2) respectively of (1) such that (ψ1, ψ2) ≤ (z1, z2). then (1) has a solution (u, v) such that (u, v) ∈ [(ψ1, ψ2), (z1, z2)].

      3 Main result

      Theorem 3.1 Suppose that (A1)-(A3) hold, then for every λ ∈ [A, B], system (1) has at least one positive solution.

      Proof of Theorem 3.1 We shall verify that (ψ1, ψ2) is a sub solution of (1.1) where
      ψ 1 = γ 1 p - 1 p - 1 p φ p p p - 1 ψ 2 = γ 1 q - 1 q - 1 q φ q q q - 1 . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Eque_HTML.gif
      Let W H 0 1 ( Ω ) http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_IEq6_HTML.gif with w ≥ 0. Then
      Ω | ψ 1 | p - 2 ψ 1 w d x = γ Ω ( λ p φ p p - | φ p | p ) w d x http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equ3_HTML.gif
      (4)
      Now, on Ω ¯ δ http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_IEq7_HTML.gif by (2),(3) we have
      γ ( λ p φ p p - | φ p | p ) - m γ http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equf_HTML.gif
      Since λB then
      λ m γ β a ( γ 1 p - 1 ) + f 0 . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equg_HTML.gif
      thus
      γ ( λ p φ p p - | φ p | p ) - m γ λ - β a ( γ 1 p - 1 ) - f 0 λ g ( x ) a ( γ 1 p - 1 ) - f 0 λ g ( x ) a p - 1 p γ 1 p - 1 φ p 1 p - 1 + f q - 1 q γ 1 q - 1 φ q 1 q - 1 http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equh_HTML.gif
      then by (4)
      Ω ¯ δ | ψ 1 | p - 2 ψ 1 w d x Ω ¯ δ λ g ( x ) a p - 1 p γ 1 p - 1 φ p p p - 1 + f q - 1 q γ 1 q - 1 φ q q q - 1 w d x http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equi_HTML.gif
      A similar argument shows that
      Ω ¯ δ | ψ 2 | q - 2 ψ 2 w d x Ω ¯ δ λ g ( x ) b q - 1 q γ 1 q - 1 φ q 1 q - 1 + h p - 1 p γ 1 p - 1 φ p 1 p - 1 w d x http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equj_HTML.gif
      Next, on Ω - Ω ¯ δ http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_IEq8_HTML.gif. Since λA, then
      λ γ λ p η a γ 1 p - 1 α p + f γ 1 q - 1 α q http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equk_HTML.gif
      so we have
      γ ( λ p φ p p - | φ p | p ) γ λ p λ η a γ 1 p - 1 α p + f γ 1 q - 1 α q λ [ g ( x ) a ( ψ 1 ) + f ( ψ 2 ) ] , Ω - Ω δ ¯ http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equl_HTML.gif
      Then by (4) on we have
      - Δ p ψ 1 λ [ g ( x ) a ( ψ 1 ) + f ( ψ 2 ) ] on Ω - Ω δ ¯ http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equm_HTML.gif
      A similar argument shows that
      - Δ q ψ 2 λ [ g ( x ) b ( ψ 2 ) + h ( ψ 1 ) ] http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equn_HTML.gif
      We suppose that κ p and κ q be solutions of
      - Δ p κ p = 1 in Ω κ p = 0 on Ω - Δ q κ q = 1 in Ω κ q = 0 on Ω http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equo_HTML.gif

      respectively, and μ' p = ||κ p ||κ, ||κ q ||κ = μ' q .

      Let
      ( z 1 , z 2 ) = c μ p λ 1 p - 1 κ p , 2 h c λ 1 q - 1 1 q - 1 λ 1 q - 1 κ q . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equp_HTML.gif

      Let W H 0 1 ( Ω ) http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_IEq9_HTML.gif with w ≥ 0.

      For sufficient C large
      μ p p - 1 [ | | g | | a ( C λ 1 p - 1 ) + f ( ( 2 h ( C λ 1 p - 1 ) ) 1 q - 1 λ 1 q - 1 μ q ) ] C p - 1 1 http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equq_HTML.gif
      then
      | z 1 | p - 2 z 1 w d x = λ C μ p p - 1 w d x λ | | g | | a ( C λ 1 p - 1 ) + f ( 2 h ( C λ 1 p - 1 ) ) 1 q - 1 λ 1 q - 1 μ q d x λ g ( x ) a ( C λ 1 p - 1 κ p μ p ) + f ( 2 h ( C λ 1 p - 1 ) ) 1 q - 1 λ 1 q - 1 κ q d x = [ g ( x ) a ( z 1 ) + f ( z 2 ) ] w d x http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equr_HTML.gif
      Similarly, choosing C large so that
      | | g | | b 2 h C λ 1 p - 1 1 q - 1 λ 1 q - 1 μ q h C λ 1 p - 1 1 http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equs_HTML.gif
      then
      | z 2 | q - 2 z 2 w d x = 2 λ h C λ 1 p - 1 w d x λ | | g | | b ( z 2 ) + h ( z 1 ) w d x . http://static-content.springer.com/image/art%3A10.1186%2F1687-2770-2011-52/MediaObjects/13661_2011_Article_97_Equt_HTML.gif

      Hence by Lemma (1.1), there exist a positive solution (u, v) of (1) such that (ψ1, ψ2) ≤ (u, v) ≤ (z1, z2).

      Declarations

      Authors’ Affiliations

      (1)
      Department of Mathematics, Science and Research Branch, Islamic Azad University
      (2)
      Department of Mathematics, Faculty of Mathematical Sciences University of Mazandaran

      References

      1. Ali J, Shivaji R: Existence results for classes of Laplacian system with sign-changing weight. Appl Math Anal 2007, 20: 558-562.MathSciNetMATH
      2. Rasouli SH, Halimi Z, Mashhadban Z: A remark on the existence of positive weak solution for a class of (p, q)-Laplacian nonlinear system with sign-changing weight. Nonlinear Anal 2010, 73: 385-389. 10.1016/j.na.2010.03.027View ArticleMathSciNetMATH
      3. Ali J, Shivaji R: Positive solutions for a class of (p)-Laplacian systems with multiple parameters. J Math Anal Appl 2007, 335: 1013-1019. 10.1016/j.jmaa.2007.01.067View ArticleMathSciNetMATH
      4. Hai DD, Shivaji R: An existence results on positive solutions for class of semilinear elliptic systems. Proc Roy Soc Edinb A 2004, 134: 137-141. 10.1017/S0308210500003115View ArticleMathSciNetMATH
      5. Hai DD, Shivaji R: An Existence results on positive solutions for class of p-Laplacian systems. Nonlinear Anal 2004, 56: 1007-1010. 10.1016/j.na.2003.10.024View ArticleMathSciNetMATH
      6. Canada A, Drabek P, Azorero PL, Peral I: Existence and multiplicity results for some nonlinear elliptic equations. A survey Rend Mat Appl 2000, 20: 167-198.

      Copyright

      © Haghaiegh and Afrouzi; licensee Springer. 2011

      This article is published under license to BioMed Central Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://​creativecommons.​org/​licenses/​by/​2.​0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.